Production and characterization of the defatted oil palm shell nanoparticles - Abdul Khalil H.P.S.,; Md. Sohrab Hossain,; Nur Amiranajwa A.S.,; Nurul Fazita M.R,; Mohamad Haafiz M.K.,; Suraya N.L.M., (Penerbit Universiti Kebangsaan Malaysia, 2016)
This present study was conducted to produce defatted oil palm shell (OPS) nanoparticles. Wherein, the OPS nanoparticles were defatted by solvent extraction method. Several analytical methods including transmission electron microscope (TEM), X-ray diffraction (XRD), particle size analyzer, scanning electron microscope (SEM), SEM energy dispersive X-ray (SEM-EDX) and thermal gravimetric analyzer (TGA) were used to characterize the untreated and defatted OPS nanoparticles. It was found that 75.3% OPS particles were converted into nanoparticles during ball milling. The obtained OPS nanoparticles had smaller surface area with angular, irregular and crushed shapes under SEM view. The defatted OPS nanoparticles did not show any agglomeration during TEM observation. However, the untreated OPS nanoparticles had higher decomposition temperature as compared to the defatted OPS nanoparticles. Based on the characterization results of the OPS nanoparticles, it is evident that the defatted OPS nanoparticles has the potentiality to be used as filler in biocomposites.